Modified titanium post with polished sidewalls and prefabricated shoulders can effectively preserve the teeth with subgingival defects - Guosheng Cui; Jie Zhang; Bohan Cui (Scientific Reports)
Abstract Objective of this study was to examine the clinical efficacy and mechanical characteristics of the modified titanium post in the restoration of subgingival defect teeth. Teeth with subgingival defects depth ≥ 2 mm were randomly restored using a fiber post after crown lengthening and a modified titanium post, respectively. Gingival index, sulcus bleeding index, probing depth, tooth mobility, and gingival papilla height were recorded before and after restoration. Tooth models with a 4 mm subgingival defect, which then underwent fiber post restoration after crown lengthening and modified titanium post restoration respectively, was established. The stresses in the tooth and tooth-supporting structures were measured under vertical and horizontal loads. The gingival index, sulcus bleeding index, and probing depth in the titanium post groups did not show significant differences compared to those of the crown lengthening group. However, the tooth mobility, gingival papilla height, and stress distribution in the tooth and periodontal tissue were significantly better in the titanium post than those in crown lengthening group. Teeth restored with modified titanium post had a healthy periodontal status, clinical efficacy and stress distribution in dental and periodontal tissues were superior to the teeth restored with crown lengthening. However, longer term observation was still needed.